Trends and Prospects in Geotechnics - Paulo J. Venda Oliveira; António Alberto S. Correia (Applied Sciences, 2022)
The Special Issue, titled “Trends and Prospects in Geotechnics”, was launched with an invitation to authors from all over the world to address current and future challenges in geotechnics [...]